Monitoring eutrophication in the Vaal Dam using satellite remote sensing - Hlahane, Keneilwe (Department of Oceanography, 2019)
The Vaal Dam is one of South Africa’s important inland water resources, however it is experiencing ecological problems related to eutrophication. The dam supplies water for domestic, industrial, mining and agricultural usage. This research aims to assess and monitor the threats of eutrophication and cyanobacterial blooms within the Vaal Dam. A 10-year archive of remotely sensed satellite data was collected from the medium resolution imaging spectrometer full resolution (MERIS FR) satellite from 2002 to 2012. Data products on chlorophyll-a, cyanobacteria concentration, cyanobacteria and surface scum percentage coverage data were derived from MERIS satellite imagery, using the maximum peak height (MPH) algorithm. The derived data products were used as indicator measures of the trophic status. This research presents a time series analysis of chlorophyll-a (a proxy for eutrophication) and cyanobacteria to establish the status, seasonality and trends for the Vaal Dam. Statistical analysis methods were applied to determine the drivers of eutrophication. In addition, the effects of climate variables on eutrophication were analyzed. Geographic Information Systems methods were applied to determine the spatial distribution and variations of chlorophyll- a. The results indicate the trophic status of the Vaal Dam ranged from being eutrophic and hypertrophic over the 10-year period. Seasonality analysis indicated that cyanobacteria blooms increased in production during the summer period and decreased in winter. Statistical analysis of the results indicated that the correlation between Chl-a and nutrients is not statistically significant. Therefore, nutrients themselves are not driving eutrophication in the Vaal Dam. The produced maps from satellite images showed the spatial distribution of Chl-a within dam. The maps indicated the eastern areas of the Vaal Dam as areas where algal and cyanobacteria blooms occur in high concentrations. The correlation between Chl-a and climate variables indicates that there is a correlation with temperature and wind speed, and an indistinct relationship with rainfall. The study concludes that both nutrient and climatic variables contribute as drivers of eutrophication within the Vaal Dam. The methods applied in this research will help to transform the satellite data into useful knowledge products, which can be used to supplement current monitoring of inland freshwater resources.